Bonded body of metal and insulator, use thereof, and method for manufacturing bonded body of metal
By miniaturizing the crystal grain size on the surface of the metal component and cooling it at low temperature, the problem of easy cracking of through terminals under low temperature and high pressure environment was solved, and the airtightness and mechanical strength were improved.
Patent Information
- Application Number
- CN202480038307.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-14
- Filing Date
- 2024-06-13
- Publication Date
- 2026-01-06
AI Technical Summary
Existing through-terminals are prone to cracking under low temperature and high pressure conditions, affecting airtightness, especially when stress is repeatedly applied.
By miniaturizing the crystal grain size on the surface of the metal component, making the average crystal grain size on the surface smaller than the internal grain size, an insulating component is bonded to the metal component using a bonding material, and the bond is solidified by low-temperature cooling treatment, thereby reducing the generation of cracks.
It improves the mechanical strength of metal components, reduces the generation and development of cracks, and ensures airtightness and joint strength under low temperature and high pressure environments.
Smart Images

Figure CN121285535A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the use of a metal-insulator joint, an airtight terminal including the joint, and a method for manufacturing a metal-insulator joint. Background Technology
[0002] Hermetic terminals, also known as gas seals, are used, for example, as inlets for signals and current entering chambers and piping requiring airtightness. A hermetic terminal typically comprises a cylindrical conductive pin, an insulating member with a through hole for insertion of the conductive pin, and a cylindrical sleeve surrounding the outer periphery of the insulating member. The conductive pin and sleeve are constructed of metal. Therefore, a highly precise bonding technique between the insulating member and the metal member is required.
[0003] Patent Document 1 describes a through-terminal comprising a cylindrical member, a plate member (equivalent to the aforementioned insulating member) made of ceramic insulating material that is hermetically joined to the inner circumference of the cylindrical member, and a pin made of conductive material that penetrates the plate member. Furthermore, Patent Document 1 describes the cylindrical member as an alloy composed of at least iron, nickel, and cobalt.
[0004] To maintain airtightness, the through-terminal in Patent Document 1 is joined by a metal tube sandwiched between a plate member made of ceramic insulating material and a pin made of conductive material such as copper. According to the description, the through-terminal can thus maintain airtightness without being affected by residual stress.
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2003-323856 Summary of the Invention
[0008] The metal-insulator joint of the present invention (hereinafter sometimes simply referred to as the "joint") has a metal member, an insulating member, and a joining material for joining the metal member and the insulating member. On the surface of the metal member, when the portion in contact with the joining material is designated as the joint, the average grain size of the surface layer of the metal member in the joint is smaller than the average grain size of the interior layer of the metal member.
[0009] The connector of the present invention is used, for example, in window components for electromagnetic wave transmission, power supply terminals, airtight terminals, etc.
[0010] The manufacturing method of the joint of the present invention includes: a preparation step, preparing an insulating component, a metal component, and a bonding material comprising metal or glass; a bonding step, bonding the insulating component and the metal component with the bonding material to form a pre-joint; and a cooling step, cooling the pre-joint at a temperature below -100°C to obtain the joint. Attached Figure Description
[0011] Figure 1 This is a perspective view of a joint body representing one embodiment of the present invention.
[0012] Figure 2 yes Figure 1 The cross-sectional view of the joint shown.
[0013] Figure 3 yes Figure 2 Enlarged sectional view of part A in the middle.
[0014] Figure 4A It means Figure 2 An enlarged sectional view of another example of the joint in part A.
[0015] Figure 4B It means Figure 2 An enlarged sectional view of another example of the joint in part A.
[0016] Figure 5A This is an enlarged sectional view showing an example that does not belong to the joint.
[0017] Figure 5B This is an enlarged sectional view showing another example that does not belong to the joint.
[0018] Figure 6 yes Figure 2 Enlarged sectional view of section B.
[0019] Figure 7A It means Figure 2 An enlarged sectional view of another example of the joint in part B.
[0020] Figure 7B It means Figure 2 An enlarged sectional view of another example of the joint in part B.
[0021] Figure 8 This is a cross-sectional view of other airtight terminals of the present invention.
[0022] Figure 9A It means Figure 2 An enlarged sectional view of another example of the joint in part A.
[0023] Figure 9B It means Figure 2 An enlarged sectional view of another example of the joint in part B.
[0024] Figure 10 These are microscopic images used to illustrate a specific method for the joining of the present invention.
[0025] Figure 11 These are microscopic images used to determine the location of the surface layer away from the joint in this invention.
[0026] Figure 12 This is a flowchart illustrating one embodiment of a method for manufacturing the assembly of the present invention.
[0027] Figure 13 This is an exploded view illustrating the assembly method of the components constituting the joint of the present invention.
[0028] Figure 14A It is a microscopic image (magnification: 1500x) obtained by photographing the crystal shape of the joint of the first metal component of the present invention.
[0029] Figure 14B It is a microscopic image (magnification: 1500x) obtained by photographing the crystal shape of the first metal component of the present invention at a position away from the joint.
[0030] Figure 15A It is a depiction Figure 14A Microscopic image showing the shape of the crystal.
[0031] Figure 15B It is a depiction Figure 14B Microscopic image showing the shape of the crystal.
[0032] Figure 16A It means Figure 15A A diagram showing the depiction of the crystal shape.
[0033] Figure 16B It means Figure 15B A diagram showing the depiction of the crystal shape.
[0034] Figure 17A It is based on Figure 15A , 15B A graph showing the variation of the average crystal grain size with respect to the distance (μm) from the surface of the first metal component.
[0035] Figure 17B It is based on Figure 15A , 15B A graph showing the refinement rate of the crystal relative to the depth percentage (%) measured from the surface of the first metal component (with the average internal crystal grain size set to 100%).
[0036] Figure 18AThe image shows the surface and interior crystal shape of the joint of the second metal component of the present invention, and a microscopic image (magnification: 1500x) depicting the crystal shape.
[0037] Figure 18B The image shows the crystal shape of the surface and interior of the second metal component of the present invention away from the joint, and a microscopic image (magnification: 1500x) depicting the crystal shape.
[0038] Figure 19A It means Figure 18A A diagram showing the depiction of the crystal shape.
[0039] Figure 19B It means Figure 18B A diagram showing the depiction of the crystal shape.
[0040] Figure 20A It is based on Figure 19A , 19B A graph showing the variation of the average crystal grain size with respect to the distance (μm) from the surface of the second metal component.
[0041] Figure 20B It is based on Figure 19A , 19B A graph showing the refinement rate of the crystal relative to the depth percentage (%) measured from the surface of the second metal component (with the average internal crystal grain size set to 100%).
[0042] Figure 21A It is a microscopic image (magnification: 1500x) of the surface and internal crystal shape of a metallic element immersed in liquid nitrogen and cooled.
[0043] Figure 21B It is a microscopic image (magnification: 1500x) that captures the surface and internal crystal shape of a metallic element that has not undergone cryogenic treatment.
[0044] Figure 22A It means Figure 21A A diagram showing the depiction of the crystal shape.
[0045] Figure 22B It means Figure 21B A diagram showing the depiction of the crystal shape.
[0046] Figure 23A It is based on Figure 21A , 21B A graph showing the variation of the average crystal grain size with respect to the distance (μm) from the surface of the metallic element.
[0047] Figure 23BIt is based on Figure 21A , 21B A graph showing the refinement rate of the crystal relative to the depth percentage (%) from the surface of the metallic element (with the average internal crystal grain size set to 100%). Detailed Implementation
[0048] Hereinafter, the joining body according to an embodiment of the present invention will be described with reference to the accompanying drawings. However, for ease of explanation, the drawings referred to below are simplified representations of embodiments of the present invention. Therefore, the joining body disclosed below may include any constituent members not shown in the referenced drawings. In addition, the dimensions of the members in the drawings do not faithfully represent the actual dimensions of the constituent members or the numerical values of the size ratios of each member.
[0049] The through-terminal described in Patent Document 1 has low mechanical strength, making it prone to cracking in the metal cylindrical components, tubes, and pins near the brazed joint when external stress is applied. This is especially true when using through-terminals in low-temperature or high-pressure environments, where large stresses are applied to the metal material near the brazed joint, easily leading to cracks in the cylindrical components, tubes, and pins. Once cracks occur in the cylindrical components, tubes, and pins, the airtightness of the through-terminal decreases. Cracks are particularly prone to occur under repeated stress.
[0050] Figure 1 This is a perspective view showing the assembly 20 of this embodiment. Figure 2 This is its sectional view. Figure 1 , 2 The connector 20 shown can be used, for example, as an airtight terminal.
[0051] The joint 20 has a metal member comprising a first metal member 2 as a cylindrical body and a second metal member 4 as a columnar body, and is joined to an insulating member 6 as an insulator. The insulating member 6 has a through hole 5 located within the inner wall of the cylindrical body of the first metal member 2. The second metal member is configured to pass through the through hole 5.
[0052] The first metal member 2 and the second metal member 4 are joined to the insulating member 6 by a bonding material 12. The insulating member 6 faces the first metal member 2 and the second metal member 4, respectively, separated by gaps 8a and 8b, and at least a portion of the bonding material 12 is located within the gaps 8a and 8b. Alternatively, the gaps 8a and 8b may be omitted at least partially, for example, by having the first metal member 2 and the second metal member 4 abut against the insulating member 6. Examples of bonding materials 12 include metals such as brazing filler metal and glass.
[0053] Figure 3 yes Figure 2 An enlarged sectional view of part A. (See example) Figure 3 As shown, the bonding material 12 that joins the first metal member 2, which includes a cylindrical body, to the insulating member 6 has a first extension portion 12a1 and a first filling portion 12a2 located within the gap portion 8a. The first extension portion 12a1 has a fillet shape that extends in a direction away from the insulating member 6 and contacts a portion of the surface of the first metal member 2 and a portion of the surface of the insulating member 6.
[0054] On the surface of the first metal member 2, the portion that contacts the joining material 12 is designated as the first joint portion 10a. Figure 3 In this case, the surface of the first metal member 2 that contacts the first extension portion 12a1 and the first filling portion 12a2 is designated as the first joint portion 10a.
[0055] Figure 2 Part A not only has, but also has, Figure 3 The shape shown also has the following characteristics: Figure 4A , 4B The shape shown. Figure 4A In the middle, the bonding material 12 only has the first filling part 12a2. Figure 4B In the middle, the bonding material 12 only has the first extension portion 12a1.
[0056] The first filling portion 12a2 needs to ensure that the bonding material 12 contacts both the first metal member 2 and the insulating member 6 within the gap portion 8a. Contact with both means that the bonding material 12 is present on the line segment within the gap portion 8a that connects the first metal member 2 and the insulating member 6 with the shortest possible distance. However, it is assumed that there are no gaps (closed gaps in the bonding material 12) that do not contact either the first metal member 2 or the insulating member 6 on the line segment. Figure 5A , 5B As shown, the first joint 10a is not the case where the bonding material 12 does not contact at least one of the first metal member 2 and the insulating member 6 (part D). Even when the bonding material 12 is in contact with both the first metal member 2 and the insulating member 6, the first joint 10a is also not the case where, except for gaps, the bonding material 12 is not present on the line segment connecting the first metal member 2 and the insulating member 6 with the shortest distance within the gap 8a.
[0057] In this embodiment, the average crystal grain size of the first surface layer 2a1 of the first metal member 2 in the first joint 10a is smaller than the average crystal grain size of the first interior layer 2b of the first metal member 2.
[0058] For example, when the average crystal grain size of the first interior 2b of the first metal component 2 is set as Di (μm) and the average crystal grain size of the first surface layer 2a1 is set as Ds (μm), it can be expressed by the formula: Ds≤0.7Di. That is, it means that the average crystal grain size Ds of the first surface layer 2a1 is less than 70% of the average crystal grain size Di of the first interior 2b. It can also have the relationship: Ds≤0.6Di.
[0059] Because the crystals are miniaturized in the first surface layer 2a1 of the first metal member 2, the mechanical strength is improved. Therefore, for example, when stress (mechanical stress, thermal stress, etc.) is applied to the first metal member 2 from the insulating member 6 through the first joint 10a, it is possible to reduce the occurrence of cracks in the first surface layer 2a1, which is the inner wall of the cylindrical body of the first metal member 2.
[0060] Because the average crystal grain size of the first interior 2b of the first metal component 2 is relatively large, even if a fine crack is generated in the first surface layer 2a1 of the first metal component 2, the propagation of the crack into the interior can be reduced. Furthermore, because the first metal component 2 has high rigidity, it is not easy to be damaged even when stress is repeatedly applied to the joint 20.
[0061] The first surface layer 2a1 of the first metal member 2 refers to the region from the surface (inner wall surface) of the first metal member 2 to a depth L of 5% relative to the thickness. For example, when the thickness of the first metal member 2, which is a cylindrical body, is 0.75 mm, the first surface layer 2a1 refers to the region from the surface to the thickness direction with a depth L of 0.0375 mm.
[0062] The first interior 2b of the first metal member 2 refers to a region whose depth from the surface (inner wall surface) of the first metal member 2 is more than 20% and less than 80% of its thickness. For example, when the thickness of the first metal member 2 is 0.75 mm, the first interior 2b is a region whose depth from the surface in the thickness direction is more than 0.15 mm and less than 0.6 mm.
[0063] Preferably, the average crystal grain size of the surface layer 2a2 of the first metal member 2 away from the first joint 10a is smaller than the average crystal grain size of the first interior layer 2b of the first metal member 2, and larger than the average crystal grain size of the first surface layer 2a1 of the first metal member 2 in contact with the first joint 10a.
[0064] Therefore, it is possible to reduce the propagation of cracks into the first interior 2b, and also to reduce the propagation of cracks into the surface layer 2a2 away from the first joint 10a. Even under repeated stress, it is possible to reduce the damage to the first metal member 2, which is a cylindrical body.
[0065] The method for determining the surface layer 2a2 away from the first joint 10a will be described later.
[0066] Figure 6 yes Figure 2 An enlarged sectional view of part B. (See example...) Figure 6 As shown, the bonding material 12 that joins the second metal member 4 containing the columnar body to the insulating member 6 has a second extension portion 12b1 and a second filling portion 12b2. The second extension portion 12b1 has a rounded corner shape that contacts a portion of the surface of the second metal member 4 extending in a direction away from the insulating member 6 and a portion of the surface of the insulating member 6. The second filling portion 12b2 is located within the gap portion 8b.
[0067] On the surface of the second metal member 4, the portion that contacts the joining material 12 is designated as the second joint portion 10b. Figure 6 In this case, the surface of the second metal member 4 at the part that contacts the second extension portion 12b1 and the second filling portion 12b2 is designated as the second joint portion 10b.
[0068] Figure 7A In the middle, the bonding material 12 only has the second filling part 12b2. Figure 7B In the middle, the bonding material 12 only has the second extension 12b1.
[0069] The second joint 10b in contact with the joint material 12 not only includes Figure 6 The forms shown also include, for example, Figure 7A and Figure 7B The shape shown.
[0070] exist Figure 6 , 7A In the joint between the second metal member 4, which includes a columnar body, and the insulating member 6, as shown in Figure 7B, the average crystal grain size of the second surface layer 4a1 of the second metal member 4 in the second joint 10b is also smaller than the average crystal grain size of the second interior layer 4b of the second metal member 4. For example, when the average crystal grain size of the second interior layer 4b of the second metal member 4 is set as Di (μm) and the average crystal grain size of the second surface layer 4a1 is set as Ds (μm), it can be expressed by the formula: Ds≤0.7Di. It can also be Ds≤0.6Di.
[0071] The second surface layer 4a1 of the second metal member 4 refers to the area from the surface of the second metal member 4 to a depth L that is 5% of the thickness (half the diameter in the case of a columnar body such as a solid pin). For example, when the diameter of the second metal member 4 is 1.6 mm (radius 0.8 mm), the second surface layer 4a1 is the area from the surface to a radial depth L of 0.04 mm.
[0072] The second interior 4b of the second metal member 4 refers to the region whose depth from the surface of the second metal member 4 is 20% or more relative to its radial thickness (half the diameter in the case of a columnar body such as a solid pin). For example, if the diameter of the second metal member 4 is 1.6 mm (radius 0.8 mm), the second interior 4b is the region that is radially deeper than 0.16 mm from the surface. The upper limit of the second interior 4b is the center C (axis) of the second metal member 4.
[0073] In the second metal member 4, the average crystal grain size of the surface layer 4a2 away from the second joint 10b is smaller than the average crystal grain size of the second interior 4b of the second metal member 4, and larger than the average crystal grain size of the second surface layer 4a1 of the second metal member 4 that is in contact with the second joint 10b.
[0074] Figure 2 The shown joint 20 is joined to the first metal member 2 and the second metal member 4 on one side (upper side) of the insulating member 6; however, it can also be joined as... Figure 8 As shown in the figure, the joint 21 is joined to the first metal member 2 and the second metal member 4 on both sides (top and bottom) of the insulating member 6.
[0075] like Figure 9A , 9B As shown, the insulating member 6 may have chamfered portions 14 on its outer peripheral surface facing the first metal member 2 and on the inner wall surface of the through hole 5 through which the second metal member 4 is inserted. The chamfered portion 14 may include at least one of the C surface and the R surface. Figure 9A , 9B The chamfered portion 14 is located on one side (upper side) of the insulating member 6, but it can also be located on both sides (upper and lower) of the insulating member 6.
[0076] The method for determining the first extension 12a1 and the second extension 12b1 is based on Figure 10 Please provide an explanation. Figure 10 This is a microscopic image showing a cross-section of the second joint 10b and its surrounding area according to the present invention. Figure 10 In this example, the second extension 12b1 (the second joint 10b) is used for explanation. However, the same determination method can be used to determine the first extension 12a1 (the first joint 10a).
[0077] (a) such as Figure 10 As shown, a first straight line L1 is drawn along the surface of the insulating member 6 and its extension. The first straight line L1 intersects the second metal member 4.
[0078] (b) Draw a second straight line L2 along the outline of the outer periphery of the second metal component 4. The second straight line L2 intersects the first straight line L1. Set the intersection of the first straight line L1 and the second straight line L2 as the origin P1.
[0079] (c) Draw out a third line L3 with the origin P1 as the starting point and an angle of 1° from the second line L2 to the second extension 12b1.
[0080] (d) The point where the outline of the third straight line L3 first intersects with the outline of the second extension 12b1 is set as point P2.
[0081] (e) Draw a fourth line L4 that is parallel to the first line L1 and passes through point P2.
[0082] The second extension 12b1 is defined as the joining material 12 located between the first straight line L1 and the fourth straight line L4. The second joining portion 10b in the second extension 12b1 is the surface of the second metal member 4 located between the first straight line L1 and the fourth straight line L4. It should be noted that, for reasons described later, the illustration is presented such that the second joining portion 10b is located between the first straight line L1 and the fifth straight line L5.
[0083] Figure 10 Since there are second extensions 12b1 on both sides of the second metal member 4, it is best to define a second joint 10b for each of the second extensions 12b1.
[0084] Although the angle between the second straight line L2 and the third straight line L3 is set to 1°, it is acceptable to choose an angle that is appropriately selected within the range of 0.8° to 1.6°. If it is within the above range, the crystals in the second surface layer 4a1 of the second joint portion 10b will be miniaturized. The second extension portion 12b1 extends thinly away from the insulating member 6 after passing through point P2; however, since it is a thin film, it is considered not to substantially participate in the bonding. Figure 10 The diagram is schematically shown in a way that makes it easy to understand how the second joint 10b is determined; in reality, point P2 is located near point P4.
[0085] It should be noted that if there is an irregular protrusion or bulge in the second extension 12b1 (especially its end portion), it is appropriate to disregard the protrusion or bulge when determining the second extension 12b1.
[0086] In cases where it is difficult to determine the second joint 10b using the aforementioned method, the portion of the extended portion with a thickness of 15 μm or more can be designated as the second extended portion 12b1. Figure 10 In this context, the thickness of the extension portion above the fifth straight line L5, which is parallel to the first straight line L1, is less than 15 μm, and it is considered that it does not substantially participate in the bonding.
[0087] If it is difficult to determine the second joint 10b using any of the above methods, it can be determined using the arc-shaped cross-sectional shape of the second extension 12b1. Figure 10 In the cross-sectional view shown, the arc C1 is drawn as close as possible to the contour of the second extension 12b1. "As close as possible" means that the difference between the arc C1 and the contour of the second extension 12b1 is minimized. The difference between the arc C1 and the contour of the second extension 12b1 can be calculated, for example, as follows: Draw a straight line from the center of the arc C1 towards the arc C1, and determine the intersection point E of the line with the arc C1 and the intersection point F of the line with the contour of the second extension 12b1. Define the direction from the center of the arc C1 towards the arc C1 as the positive direction, and define the length of the line from intersection point E to intersection point F as the difference between the contour of the arc C1 and the contour of the second extension 21b. For example, draw nine straight lines from the center of arc C1, dividing arc C1 into nine equal parts. Calculate the difference between arc C1 and the contour of the second extension 12b1 on each line. The state where the sum of these differences is minimized is defined as the minimum difference between arc C1 and the second extension 12b1. The number of equal parts to divide arc C1 can be adjusted appropriately according to the shape of the second extension 21b. The circumference of arc C1 is set to 1 / 4 of the circumference of a circle. Arc C1 has points P3 and P4 at both ends. Point P4 on arc C1 is the point closest to the second metal component 4. Through point P4 on arc C1, draw a sixth straight line L6 parallel to the first straight line L1. Figure 10 (It coincides with the fifth straight line L5). At this time, the second joint 10b is located between the first straight line L1 and the sixth straight line L6.
[0088] The first extension 12a1 is also determined using the same determination method.
[0089] The method for determining the surface layer 4a2, which is far from the second joint 10b, is based on Figure 11 Please provide an explanation.
[0090] (1) The upper end of the second joint 10b is designated as the starting end (0mm). This includes the starting end portion and several portions along the surface of the second metal member 4 away from the starting end (e.g., such as...). Figure 11 The average crystal grain size of the surface layer and the second interior layer 4b of the second metal component 4 were measured in multiple sections spaced at 0.25 mm intervals.
[0091] (2) Calculate the miniaturization rate (%) of the crystal using the following formula.
[0092] Formula: Miniaturization rate (%) = {(Average crystal grain size on the surface) / (Average crystal grain size inside)} × 100
[0093] The calculation results are shown in Table 1. The surface and interior are as described above.
[0094]
[0095] The measurement interval is not limited to 0.25 mm and can be changed appropriately.
[0096] (3) According to Table 1 above, the area that is far from the beginning (0 mm), has a fineness rate (%) greater than the beginning, and has a fineness rate (%) greater than 80% (i.e., the area containing the measurement positions of 0.75 mm, 1.00 mm and 1.25 mm) is designated as the surface layer 4a2 far from the second joint 10b.
[0097] The surface layer 2a2, which is away from the first joint 10a, can be determined using the same determination method as the surface layer 4a2, which is away from the second joint 10b.
[0098] right Figure 1 , 2 The manufacturing method of the shown joint 20 will be described. Figure 12 This is a flowchart illustrating the manufacturing method. Figure 13 It is an exploded diagram showing the assembly method of each component.
[0099] like Figure 12 As shown, in manufacturing the joint of the present invention, the insulating member 6, the metal member (the first metal member 2 and the second metal member 4) and the joint material 12 containing metal or glass are prepared as raw materials (preparation step).
[0100] An insulator is defined as a material with an inherent volume resistivity of 10 Ω at 20°C. 10 Insulating materials with an Ω·m or higher.
[0101] The insulating component 6 is preferably composed of any one of alumina, zirconium dioxide, silicon nitride, silicon carbide, forsterite, cordierite, and sapphire. The ceramic material in these insulating components 6 is inexpensive and has excellent mechanical strength, while sapphire has excellent light transmittance.
[0102] The principal component of an insulating component refers to the component that accounts for 60% or more of the total 100% by mass of the components constituting the insulating component. In particular, the principal component should preferably be the component that accounts for 95% or more of the total 100% by mass of the components constituting the insulating component. The components constituting the insulating component can be determined using an X-ray diffraction (XRD) apparatus. Regarding the content of each component, after identifying the components, the elemental content of the constituting components can be determined using an X-ray fluorescence (XRF) apparatus or an inductively coupled plasma optical emission spectrophotometer, and then converted into the identified components.
[0103] To reduce residual stress arising from the bonding with the insulating member 6 and to decrease the coefficient of thermal expansion, the first metal member 2 and the second metal member 4 preferably contain Fe, Ni, and Co, and the total content of Fe, Ni, and Co is 99% by mass or more. This reduces the likelihood of cracking of the first metal member 2 and the second metal member 4. In this case, the insulating member 6 can be mainly composed of alumina, whose coefficient of thermal expansion is similar to that of the first metal member 2 and the second metal member 4. In the first metal member 2 and the second metal member 4, Fe is preferably 40% by mass or more and 56% by mass or less, Ni is preferably 25% by mass or more and 40% by mass or less, and Co is preferably 10% by mass or more and 30% by mass or less. More specifically, Fe is preferably 50% by mass or more and 56% by mass or less, Ni is preferably 26% by mass or more and 33% by mass or less, and Co is preferably 14% by mass or more and 20% by mass or less.
[0104] Specifically, the first metal component 2 can be an Fe-Ni alloy such as Invar 36 (Fe54 wt%, Ni36 wt%) or an Fe-Ni-Co alloy such as Kovar (Fe53 wt%, Ni29 wt%, Co17 wt%).
[0105] The columnar second metal component 4 can be made of the same metal as the first metal component 2 described above. Alternatively, the second metal component 4 can be made of a different metal than the first metal component 2, such as Cu (copper) or an alloy with Cu as the main component.
[0106] Alternatively, the first metal component 2 can be Cu or an alloy with Cu as the main component, and the second metal component 4 can be an alloy such as Kovar or Invar 36.
[0107] The bonding material 12 may include metals such as brazing filler metal or glass.
[0108] As an example of a combination in this invention, it is suitable that at least one of the first metal member 2 and the second metal member 4 comprises a composition of Fe of 40% or more and 56% or less by mass, Ni of 25% or more and 40% or less by mass, and Co of 10% or more and 30% or less by mass, the insulating member 6 comprises aluminum oxide, and the bonding material 12 comprises brazing filler metal, the brazing filler metal comprising Ag and Cu, and the total content of Ag and Cu is 90% or more by mass.
[0109] After the preparation process, such as Figure 13As shown, a columnar second metal member 4 is inserted into the through hole 5 of the insulating member 6, and the insulating member 6 is inserted into the cylindrical first metal member 2. A bonding material 12 is disposed on any one of the opposing surfaces of the insulating member 6 and at least the first metal member 2, and on at least one surface of the insulating member 6 near the opposing surfaces, and on any one of the opposing surfaces of the insulating member 6 and at least the second metal member 4, and on at least one surface of the insulating member 6 near the opposing surfaces, to obtain an assembly (assembly process).
[0110] The assembly is heated in a vacuum or inactive gas to melt the bonding material 12, and then cooled to below 200°C to solidify the bonding material 12. Thus, a pre-joined body (joining process) is obtained in which the insulating member 6 is joined to the first metal member 2 and the insulating member 6 is joined to the second metal member 4.
[0111] Before applying the bonding material 12, a metallization layer can be pre-formed on the insulating member 6. Examples of metallization layers include Mo-Mn based metallization layers. After forming the metallization layer, a plating layer can be formed on it. This plating layer includes a Ni plating layer. Regardless of whether the metallization layer is formed, a plating layer can be formed on at least one of the inner wall surface of the first metal member 2 and at least the outer peripheral surface of the second metal member 4. This plating layer includes a Ni plating layer.
[0112] The pre-bonded body is cooled at an atmosphere temperature below -100°C to obtain the bonded body 20 (cooling process). By cooling the pre-bonded body, the crystal structure of the portions of the first metal member 2 and the second metal member 4 that abut against the joint (i.e., the portions of the first surface layer 2a1 and the second surface layer 4a1) can be refined. If the metal crystal structure is refined, the mechanical strength of the refined portion is improved, the generation of cracks in the first joint 10a and the second joint 10b is reduced, and the mechanical strength of the bonded body 20 between the metal and the ceramic, which is an insulator, is improved, thereby reducing the risk of failure.
[0113] Cooling can be achieved, for example, by immersion in a coolant at a temperature below -100°C. Examples of coolants include liquid oxygen (boiling point -183°C), liquid nitrogen (boiling point -196°C), liquid hydrogen (boiling point -253°C), and liquid helium (boiling point -269°C). The immersion time can be 1 minute or more, or 10 minutes or more. The pre-bonded assembly can also be cooled to below -100°C in a gaseous atmosphere, not in a liquid. By extending the immersion time, the average crystal grain size of the first surface layer 2a1 and the second surface layer 4a1 can be reduced. The immersion time can be appropriately adjusted to achieve the desired average crystal grain size.
[0114] The joint 20 of the present invention does not involve the entire metal, but rather the metal crystals of the first surface layer 2a1 and the second surface layer 4a1 of the first joint portion 10a and the second joint portion 10b are made finer compared to other parts. This is because residual stress is generated in the first surface layer 2a1 and the second surface layer 4a1 of the first joint portion 10a and the second joint portion 10b due to the joint.
[0115] The bonding body of the present invention can be used as a window member for transmitting electromagnetic waves, such as introducing electromagnetic waves into a semiconductor manufacturing apparatus or outputting high frequencies from an accelerator. This window member has a structure in which a cylindrical first metal member 2 is formed, and the outer peripheral surface of an insulating member 6 is joined to the inner wall surface of the first metal member 2. The aforementioned second metal member 4, which includes a columnar body, is not essential. The insulating member 6 is preferably composed primarily of alumina, zirconium dioxide, silicon nitride, silicon carbide, forsterite, cordierite, and sapphire.
[0116] When the insulating component 6 is made of sapphire, the electromagnetic wave transmission window component can also be used as an observation window. The observation window is used, for example, as a window for visually confirming the interior of equipment such as containers, piping, semiconductor manufacturing apparatus, and furnaces.
[0117] The connector of the present invention can also be used as a power supply terminal. For example, a power supply terminal is used in a device for introducing a large current of 100A or more. This power supply terminal has a second metal member 4 comprising a columnar body, and the aforementioned insulating member 6 has a through hole 5 through which the second metal member 4 passes. The aforementioned cylindrical first metal member 2 is not essential.
[0118] The connector of the present invention can also be used as a highly airtight terminal in the aforementioned power supply terminals. Airtight terminals are used, for example, as power supply terminals for introducing current from the outside into a vacuum container, and as signal terminals for transmitting signals from sensors located inside airtight containers, piping, equipment, etc., to the outside. Such airtight terminals... Figure 1 , 2 As shown in Figures 8 and 9, the insulating member 6 is located inside the inner wall of the cylindrical body of the first metal member 2 and has a through hole 5 through which the columnar second metal member 4 passes.
[0119] In the connectors 20 and 21 used in the airtight terminal, it is suitable that: the first metal member 2 and the second metal member 4 contain a composition of 40% or more and 56% or less Fe, 25% or more and 40% or less Ni, and 10% or more and 30% or less Co; the insulating member 6 contains alumina; and the bonding material 12 contains brazing filler metal containing Ag and Cu, wherein the total content of Ag and Cu is 90% or more.
[0120] Therefore, the airtightness between the cylindrical body of the first metal member 2 and the insulating member 6, and between the columnar body of the second metal member 4 and the insulating member 6, is excellent, and the bonding strength between them is also excellent. This is because the coefficients of thermal expansion of the first metal member 2, the second metal member 4, and the insulating member 6 are similar, and the wettability of the bonding material 12 is good. Therefore, even under applied stress, it is not easy for the first metal member 2 and the second metal member 4 to crack.
[0121] Even when used in environments below -100°C, the airtight terminal exhibits excellent airtightness and can reduce the breakage of the first metal component 2, the second metal component 4, and the insulating component 6 that constitute the airtight terminal.
[0122] The miniaturization of crystals will be described in detail below with examples.
[0123] (Example 1)
[0124] Making with Figure 8 The cross-sectional structure of the joint 21 shown is investigated, and the first joint 10a of the cylindrical first metal member 2 is studied (see reference). Figure 9A The crystals of the 21 are miniaturized. The components constituting the joint 21 are shown below.
[0125] Metal component 2: A cylindrical body (sleeve) with a thickness of 0.75 mm made of Fe-Ni-Co alloy (containing 53% by mass of Fe, 29% by mass of Ni, and 17% by mass of Co in Kovar).
[0126] Second metal component 4: A 1.6 mm diameter column (pin) made of the same Fe-Ni-Co alloy as the first metal component 2.
[0127] Insulating component 6: is a sintered body containing 99.5% by mass of alumina, having two through holes 5 for the second metal component 4 to be inserted.
[0128] Bonding material 12: a solder containing Ag and Cu, wherein the total content of Ag and Cu is 90% by mass or more.
[0129] After assembly, the assembly 21 is immersed in liquid nitrogen at -100°C for 10 minutes.
[0130] The cryogenically treated assembly 21 was embedded in resin and then cut with a diamond cutting tool. The cut surface was coarsely ground with a diamond grinding wheel, then polished with diamond abrasive grains, and finally polished with silica abrasive grains. This resulted in a mirror-like finish. The polished surface was then chemically ground with a 5% nitric acid-ethanol mixture or aqua regia (a liquid obtained by mixing concentrated nitric acid and concentrated hydrochloric acid in a volume ratio of 3:1). Alternatively, physical grinding can be performed by focused ion beam (FIB) processing, ion milling, or other methods instead of chemical grinding. This facilitates the observation of the metal grain boundaries. A cross-section of the treated sample was photographed using a microscope (Keyence VHX-5000, 1500x magnification).
[0131] Figure 14A , 14B It is a microscopic image obtained by photographing the cross-section of the cylindrical body, which is the first metal component 2, showing the crystal shape. Figure 14A The crystal shape of the first metal member 2 in the first joint 10a is shown from the first surface layer 2a1 to the first interior layer 2b. Figure 14B The crystal shape of the first metal member 2 from the surface layer 2a2 to the interior is shown at a position away from the first joint 10a (normal part). Figure 14A , 14B In the diagram, the horizontal direction represents the depth direction of the first metal component 2 from its surface, and the vertical direction (i.e., the direction along the surface of the first metal component 2) represents the direction for measuring the average crystal grain size.
[0132] The part is usually located 1 mm away from the surface of the insulating member 6 that is joined to the first metal member 2.
[0133] Figure 15A , 15B They are respectively depicted Figure 14A , 14B The image shows a microscopic image of the crystal shape. That is, Figure 15A , 15B It is by... Figure 14A , 14B The microscopic image shown is created by importing electronic data into PowerPoint (a Microsoft trademark) and using drawing tools to trace the outline of the crystal. Alternatively, the microscopic image can be printed by covering the surface with a thin sheet of paper and tracing the outline of the crystal onto that paper.
[0134] Figure 16A , 16B They represent Figure 15A , Figure 15B A diagram showing the depiction of the crystal shape.
[0135] The average crystal grain size was measured at a distance d (μm) in the depth direction from the surface and its percentage (%). The percentage (%) in the depth direction was calculated using the thickness of the first metal component 2 (0.75 mm) as 100%, according to the formula: (d / 0.75) × 100. The measurement locations expressed as percentages in the depth direction were arbitrarily set to 1.6%, 3.2%, 5.0%, 7.5%, 10%, 15%, 20%, 30%, 40%, 50%, and 65%. These measurement locations were at... Figure 16A , 16B The tracing diagram is represented by vertical lines parallel to the direction of the average crystal grain size measurement.
[0136] exist Figure 16A , 16B At each measurement location on the tracing diagram, a straight line of 150 μm is drawn along the measurement direction of the average crystal grain size. The value obtained by subtracting 1 from the total number of points where this line intersects with the grain boundaries is taken as the crystal count value. The number obtained by dividing the length of the line 150 μm by the crystal count value is taken as the average crystal grain size.
[0137] The locations where the average crystal grain size was measured are described. Figure 8 The diagram shows four first extensions 12a1 that join the left and right first metal members 2 with the insulating member 6. The measurement locations are four locations at the first joints 10a that are in contact with each first extension 12a1, and four locations at the normal portions away from each first joint 10a. The average crystal grain size at each measurement location is the average of the average crystal grain size at the four locations. The results are shown in Table 2 and... Figure 17A middle. Figure 17A The graph shows the variation of the average crystal grain size with respect to the distance from the surface (μm), that is, the distance in the depth direction measured from the surface (μm).
[0138]
[0139] Table 3 is a table showing the crystal refinement rate based on the measurement results in Table 2, calculated from the average crystal grain size at various measurement locations from the surface to 15% depth of the first metal component 2 and the average crystal grain size in the interior (the region from the surface to a depth of 20% to 65%). The crystal refinement rate is calculated using the following formula.
[0140] Formula: Miniaturization rate (%) = {(Average crystal grain size at each measurement location) / (Average crystal grain size inside)} × 100
[0141] Figure 17B The graph shows the change in the crystal miniaturization rate relative to the depth percentage from the surface (%).
[0142]
[0143] Table 4 is based on the measurement results in Table 2. The crystal refinement rate is calculated according to the average crystal grain size of the surface layer (the region from the surface to a depth of 5%) and the interior layer (the region from the surface to a depth of 20% to 65%) of the first metal component 2. The crystal refinement rate is calculated using the following formula.
[0144] Formula: Miniaturization rate (%) = {(Average crystal grain size on the surface) / (Average crystal grain size inside)} × 100
[0145]
[0146] As can be clearly seen from Table 4, the average crystal grain size of the first surface layer 2a1 of the first joint 10a is smaller than that of the first interior layer 2b. The average crystal grain size of the surface layer of the normal portion is also smaller than that of the interior layer, but the average crystal grain size is larger than that of the first surface layer 2a1 of the first joint 10a. The crystal refinement rate of the normal portion is 90%, which is essentially no refinement, while the refinement rate of the first surface layer 2a1 of the first joint 10a is 69%.
[0147] (Example 2)
[0148] Using the joint 21 used in Example 1, the second joint 10b of the columnar second metal member 4 joined to the insulating member 6 was studied (see reference). Figure 9B Miniaturization of crystals in ).
[0149] Figure 18A , 18B It is a microscopic image obtained by photographing the crystal shape of the cross-section of the columnar body (pin) which is the second metal component 4. Figure 18A This indicates the crystal shape of the second metal member 4 in the second joint 10b, from the second surface layer 4a1 to the second interior layer 4b. Figure 18B These figures depict the crystal shape of the second metal member 4 from the surface 4a2 to the interior at a location away from the second joint 10b (normal part). Figure 19A , 19B They represent Figure 18A , 18B A diagram showing the depiction of the crystal shape.
[0150] The locations where the average crystal grain size was measured are described. Figure 8The diagram shows eight second extensions 12b1 that join the left and right second metal members 4 to the insulating member 6. Measurement locations are four locations of the second joint portions 10b that are in contact with the two second extensions 12b1 that join the upper surface of the left second metal member 4 to the insulating member 6, and the two second extensions 12b1 that join the lower surface of the right second metal member 4 to the insulating member 6, and four locations of the normal portion away from each second joint portion 10b. The average crystal grain size at each measurement location is the average of the average crystal grain size at the four locations. Otherwise, the experiment was conducted using the same method as in Example 1. The results are shown in Table 5.
[0151] The average grain size of the second joint 10b and the normal portion away from it in the joint that did not undergo cryogenic treatment was also tested using the same method. The results are shown in Table 6.
[0152] Figure 20A The graphs shown are the results of Tables 5 and 6, illustrating the variation of the average crystal grain size with respect to the distance (μm) from the surface.
[0153]
[0154]
[0155] Tables 7 and 8 show the crystal refinement rate based on the measurement results in Tables 5 and 6, calculated using the average crystal grain size at various measurement locations from the surface to a depth of 15% of the second metal component 4, and the average crystal grain size inside (the region with a depth of 20% or more but less than 65% from the surface). The crystal refinement rate is calculated using the following formula.
[0156] Formula: Miniaturization rate (%) = {(Average crystal grain size at each measurement location) / (Average crystal grain size inside)} × 100
[0157] Figure 20B The graphs are charts representing the results of Tables 7 and 8, showing the change in the average crystal grain size relative to the percentage of depth from the surface.
[0158]
[0159]
[0160] Tables 9 and 10 show the crystal refinement rate based on the measurement results in Tables 7 and 8, calculated according to the average crystal grain size of the surface layer (the region from the surface to a depth of 5%) and the interior layer (the region from the surface to a depth of 20% and 65%) of the second metal component 4. The crystal refinement rate is calculated using the following formula.
[0161] Formula: Miniaturization rate (%) = {(Average crystal grain size on the surface) / (Average crystal grain size inside)} × 100
[0162]
[0163]
[0164] These experimental results clearly show that in the joint treated with liquid nitrogen at low temperature, the crystals of the second surface layer 4a1 in the second joint 10b are miniaturized (crystal miniaturization rate is 61%), and the miniaturization rate of the second surface layer 4a1 is 56-67% when the average crystal grain size of the second interior 4b is set to 100%. On the other hand, in the normal part, the miniaturization rate is 86%, and crystal miniaturization is basically not observed.
[0165] In addition, in the joint without low-temperature treatment, the miniaturization rate of the joint is 94%, and the miniaturization rate of the general part is about 96%. In fact, the crystals of the surface part are not miniaturized.
[0166] (Example for reference)
[0167] Using columnar elemental metal of the same material as the second metal component 4 used in Examples 1 and 2, the crystal refinement of samples subjected to cryogenic treatment by immersion in liquid nitrogen at -100°C for 10 minutes was investigated. Four arbitrary locations were used for measurement. Additionally, for comparison, crystal refinement was also investigated for samples that did not undergo cryogenic treatment.
[0168] Figure 21A , 21B These are microscopic images obtained by photographing cross-sections of metallic elements that have undergone cryogenic treatment and those that have not, depicting the crystal shapes. The crystal shapes are shown in these images. Figure 22A , 22B They represent Figure 21A , 21B A diagram showing the depiction of the crystal shape.
[0169] The average crystal grain size was determined and the miniaturization rate was calculated using the same method as in Example 1. The results are presented in Tables 11, 12, and 13. Figure 23A , 23B middle.
[0170]
[0171]
[0172] As shown in Tables 11, 12, 13 and Figure 23A , 23BAs shown, no crystal refinement was observed in either the metal element that underwent low-temperature treatment or the metal element that did not undergo low-temperature treatment.
[0173] The embodiments of the present invention have been described above. However, the joint of the present invention is not limited to the above embodiments and various modifications and improvements can be made.
[0174] Explanation of reference numerals in the attached figures
[0175] 2 First metal component, 2a1 First surface layer, 2b First interior layer, 2a2 Surface layer away from the first joint, 4 Second metal component, 4a1 Second surface layer, 4b Second interior layer, 4a2 Surface layer away from the second joint, 5 Through hole, 6 Insulating component, 8a, 8b Gap portion, 10a First joint, 10b Second joint, 12 Joint material, 12a1 First extension portion, 12a2 First filling portion, 12b1 Second extension portion, 12b2 Second filling portion, 14 Chamfer portion, 20 Joint body.
Claims
1. A metal-insulator bonded body, comprising: a metal member, an insulating member, and a bonding material that bonds the metal member and the insulating member, wherein, at a surface of the metal member, when a portion that comes into contact with the bonding material is set as a bonding portion, an average crystal grain size of a surface layer of the metal member in the bonding portion is smaller than an average crystal grain size of an inside of the metal member.
2. The metal-insulator bonded body according to claim 1, wherein the insulating member and the metal member face each other with a gap portion interposed therebetween, and at least a portion of the bonding material is located in the gap portion.
3. The metal-insulator bonded body according to claim 1, wherein the bonding material has a rounded shape that extends along a surface of the metal member in a direction away from the insulating member, and that comes into contact with a portion of the surface of the metal member and a portion of a surface of the insulating member.
4. The metal-insulator bonded body according to claim 2, wherein the bonding material has a rounded shape that extends along a surface of the metal member in a direction away from the insulating member, and that comes into contact with a portion of the surface of the metal member and a portion of a surface of the insulating member.
5. The metal-insulator bonded body according to any one of claims 1 to 4, wherein an average crystal grain size of a surface layer of the metal member away from the bonding portion is smaller than the average crystal grain size of the inside of the metal member, and is larger than the average crystal grain size of the surface layer of the metal member in the bonding portion.
6. The metal-insulator bonded body according to any one of claims 1 to 4, wherein the metal member has a first metal member that includes a cylindrical body, and the insulating member is located in an inner wall of the cylindrical body of the first metal member.
7. The metal-insulator bonded body according to any one of claims 1 to 4, wherein the metal member has a second metal member that includes a columnar body, the insulating member has a through-hole, and the second metal member is disposed so as to pass through the through-hole.
8. The metal-insulator bonded body according to any one of claims 1 to 4, wherein the metal member has a first metal member that includes a cylindrical body and a second metal member that includes a columnar body, the insulating member has a through-hole while being located in an inner wall of the cylindrical body of the first metal member, and the second metal member is disposed so as to pass through the through-hole.
9. The metal-insulator bonded body according to any one of claims 1 to 4, wherein the metal member contains Fe, Ni, and Co, and a total content of the Fe, the Ni, and the Co is 99 mass% or more.
10. The metal-insulator bonded body according to any one of claims 1 to 4, wherein the insulating member has any one of alumina, zirconia, silicon nitride, silicon carbide, forsterite, cordierite, and sapphire as a main component.
11. The metal-insulator bonded body according to any one of claims 1 to 4, wherein the bonding material includes a metal or glass. 12. The metal and insulator bonded body according to any one of claims 1 to 4, wherein the metal member contains 40 mass% or more and 56 mass% or less of Fe, 25 mass% or more and 40 mass% or less of Ni, and 10 mass% or more and 30 mass% or less of Co, the insulating member contains alumina, and the bonding material contains a solder containing Ag and Cu, and the total content of the Ag and the Cu is 90 mass% or more.
13. A window member for electromagnetic wave transmission, which uses the bonded body according to claim 10.
14. A power supply terminal, which uses the bonded body according to claim 7.
15. A hermetic terminal, which uses the bonded body according to claim 8.
16. A hermetic terminal, which uses the bonded body according to claim 12.
17. The hermetic terminal according to claim 16, which is used in an environment of -100°C or lower.
18. A method for producing a metal and insulator bonded body, the method comprising: a preparation step of preparing a metal member, an insulating member, and a bonding material containing a metal or glass; a bonding step of producing a pre-bonded body by bonding the insulating member and the metal member with the bonding material; and a cooling step of obtaining a bonded body by cooling the pre-bonded body at an atmospheric temperature of -100°C or lower.
19. The method for producing a metal and insulator bonded body according to claim 17, wherein the cooling is performed by immersing the pre-bonded body in a liquid containing any one of liquid nitrogen, liquid oxygen, and liquid hydrogen as a main component.
Citation Information
Patent Citations
Through terminal and x-ray tube
JP2003323856A